WATER ECOLOGY AND HYGIENE IN THE SAMARKAND REGION: PROBLEMS AND PROSPECTS - Yunusov Khudaynazar Beknazarovich; Berdiev Doniyor (Journals Park Publishing, 2024)
The article addresses the pressing issue of the environmental state of water resources in the city of Samarkand. It analyzes the main causes of water scarcity and pollution, such as the irrational use of water resources, insufficient development of water supply and sewage infrastructure, as well as the impact of climate change. Special attention is given to the problems of soil salinization and the deterioration of drinking water quality. The article suggests possible solutions to these problems, including the optimization of water usage, modernization of wastewater treatment facilities, reclamation of saline soils, and raising public environmental awareness.
Keywords: Samarkand region, ecology, water hygiene, water scarcity, water pollution, reclamation, water supply, sewage, sustainable development.